2016
DOI: 10.1097/icb.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Neovascularization Secondary to Alexandrite Laser Exposure

Abstract: The present case documents development and management of subretinal hemorrhage associated with choroidal neovascularization following macular photic trauma after accidental occupational to a 750-nm Alexandrite laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…However, the injury had affected the visual acuity and was irreversible, owing to the foveal localization of the lesion. Recently, Wang et al 11 have reported a case presented with immediate vision loss in the eye after accidentally Alexandrite laser exposure during laser hair removal without appropriate eye protection. In this case, there was subretinal hemorrhage associated with choroidal neovascularization and similarly to our case, the visual field defect was irreversible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the injury had affected the visual acuity and was irreversible, owing to the foveal localization of the lesion. Recently, Wang et al 11 have reported a case presented with immediate vision loss in the eye after accidentally Alexandrite laser exposure during laser hair removal without appropriate eye protection. In this case, there was subretinal hemorrhage associated with choroidal neovascularization and similarly to our case, the visual field defect was irreversible.…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal neovascularization was not observed in the follow-up but it has been described in the first three weeks after foveal exposure to laser beams. When present, treatment with 1 to 5 doses of intravitreal bevacizumab [8] or ranibizumab [9] has been used with excellent anatomical and visual outcomes. Cystoid macular edema (CME) has also been described as a complication of macular photocoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…There are previous reports of retinal injuries and choroidal neovascularization secondary to alexandrite laser exposure. A patient developed choroidal neovascularization and sub-retinal haemorrhage which resolved after administration of five intravitreal ranibizumab injections and some others developed sub-retinal haemorrhage with associated sub-retinal fluid, which resolved after a single dose of intravitreal injection of bevacizumab 1.25 mg/0.05 ml [13,14].…”
Section: Discussionmentioning
confidence: 99%